Unraveling the success and failure of mode coupling theory from consideration of entropy - Nandi, Manoj Kumar; Banerjee, Atreyee; Sengupta, Shiladitya; Sastry, Srikanth; Bhattacharyya, Sarika Maitra (Journal of Chemical Physics, 2015)
We analyze the dynamics of model supercooled liquids in a temperature regime where predictions of mode coupling theory (MCT) are known to be valid qualitatively. In this regime, the Adam-Gibbs (AG) relation, based on an activation picture of dynamics, also describes the dynamics satisfactorily, and we explore the mutual consistency and interrelation of these descriptions. Although entropy and dynamics are related via phenomenological theories, the connection between MCT and entropy has not been argued for. In this work, we explore this connection and provide a microscopic derivation of the phenomenological Rosenfeld theory. At low temperatures, the overlap between the MCT power law regime and AG relation implies that the AG relation predicts an avoided divergence at T-c, the origin of which can be related to the vanishing of pair configurational entropy, which we find occurring at the same temperature. We also show that the residual multiparticle entropy plays an important role in describing the relaxation time. (C) 2015 AIP Publishing LLC.